A prospective multilevel examination of the relationship between cohesion and team performance in elite youth sport - Benson, A. J.; Siška, P.; Eys, M.; Priklerová, S.; Slepicka, P. (Psychology of Sport and Exercise, 2016)
Abstract: The purpose of the current research was to (a) develop and establish the factor structure of the Czech and Slovak versions of the Youth Sport Environment Questionnaire (YSEQ; Eys, Loughead, Bray, & Carron, 2009) and (b) examine the relationship between team performance and cohesion with a sample of European elite youth sport teams. At time point one, with 352 elite youth athletes from 22 teams, support was obtained for a two factor structure underlying the YSEQ. Based on data collected at the second (N=291) and third (N=246) time points, multilevel analyses revealed that, when controlling for midseason cohesion, midseason team performance significantly and positively predicted task and social cohesion later in the season. Neither task nor social cohesion predicted team performance. In addition to adapting the YSEQ for use in a unique context, these findings reveal the nature of the cohesion-performance relationship in elite youth sport.